Assessment of Acute Toxic Effects of Tetrabromobisphenol A on Brine Shrimp and Chlorella sp. - Noorani, Peer Muhamed; Kannan, Velu Rajesh; Nooruddin, Thajuddin (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Tetrabromobisphenol A (TBBPA) is a common brominated flame retardant used in multiple consumer products, such as electronic devices, textile materials, and plastics. Its's high utilization makes it widespread in aquatic ecosystems which raising concerns regarding its possible impacts on the environment. Due to its serious threats to human health and the environment, it has become a major concern for the entire population. The objectives of this study were thereby to morphologically investigate the acute toxicity of TBBPA on two aquatic organism brine shrimp and Chlorella sp. The results indicated that the addition of TBBPA noticeably inhibited the growth of Chlorella sp. with inhibition rates between 40 at the concentration of 6 mg/L. Additionally, TBBPA disrupted the intracellular chloroplast structure at the individual level. Subsequently, Artemia salina was treated with TBBPA, which resulting a moderate mortality rate of 58% after 24 hours. The LC₅₀ and LC₉₀ were measured as 128.21 μg/mL (range: 107.86–182.17 μg/mL) and 189.58 μg/mL (range: 150.43–299.35 μg/mL), respectively. This result demonstrates the toxicity of TBBPA against Artemia salina and chlorella sp. further it can pose a higher risk to aquatic environment.